Misi bagi Perkembangan Gereja Kristen dalam Zaman Modern - Sebayanti Gamerakai; Nurlisa Potmo; Malik Bambangan (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2024)
This article discusses the role of missions in the development of Christian churches in the world. Church development in question is the growth of the congregation's faith and the addition of souls in church members through repentance and belief in Jesus Christ as personal Lord and Savior. Especially in changing times which have become modern with the development of technology, there are many challenges to the faith faced by churches, so the message of the Gospel is needed to support, strengthen and maintain the faith. This mission was started by Jesus Christ through His ministry and must be carried out because it is considered the great commission conveyed in Matthew 28:19. In discussing this article, the author uses qualitative methods through literature research studies on books and scientific papers in the form of articles related to the discussion of this article. Aims to provide new insights for readers and appeal to Christian churches to continue carrying out evangelistic missions using various methods both online and using technological media.